Relasi Manusia Dengan Alam: Kritik Terhadap Pandangan Sallie Mcfague Mengenai Tubuh Allah - Roby Handoko; Benyamin F. Intan (STTRII, 2022)
This paper will criticize one kind of approach taken by Sallie McFague on the concept of the Body of God to explain the relationship between humans and nature. This evaluation was carried out because the approach taken by McFague is an approach that seeks to revise Christian orthodoxy which is considered unfriendly to the environment and is not sufficient to answer the problem of the ecological crisis. Some of the revisions made by McFague are the story of the creation and incarnation of Christ. Through this paper, it will be evaluated whether the story of creation and incarnation needs to be revised to answer the problem of the ecological crisis.